The Performance of Indonesia’s Election Organizers in a Collaborative Management Framework - Aris Tri Haryanto,; Chandra Adjie Prianggodo,; Winarti, (Technium Social Sciences Journal, 2025)
The purpose of this study is to determine the performance of the organizers of the 2024 Indonesian elections within the framework of collaboration management. This research is important because the facts on the ground show a series of varied problems that obscure the quality of the organizers, namely the KPU, Bawaslu, and DKPP. The further substance of this research is to find out the level of organizers who are actually still far from ideal. Moreover, in the framework of institutional collaboration, which is actually part of an effort to realize public policy, but has not been matched by the competence of election institutions. This research method uses a literature study, whose urgency focuses on the researcher's ability to combine references, theories, and other supporting literature to strengthen the analysis to the findings. The use of the literature study method is important in building a scientific framework, because it utilizes scientific elements from (1) books, (2) journals, (3) newspapers, (4) media news, (5) survey reports, etc. The results of the study show that the performance of the organizers of the 2024 elections is still weak. Weaknesses are evidenced in the pre-election and post-election stages. There are driving and inhibiting factors that weaken performance, one of which is the absence of institutional collaboration management. KPU, Bawaslu, and DKPP still seem to work individually, and a lot of time is spent focusing on internal problems, morals, and codes of ethics of each institution.